Pengaruh Food Content, E-Wom, Perceived Value, dan Trust terhadap Purchase Intention Makanan Viral Instagram pada Generasi Z di JakartaPengaruh Food Content, E-Wom, Perceived Value, dan Trust terhadap Purchase Intention Makanan Viral Instagram pada Generasi Z di Jakarta - Cindy Claudya Oktaviani; Corry Yohana; Sefrimel Angriani ZN (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to analyze the direct effects of food content, E-WOM, perceived value, and trust on the purchase intention of Instagram viral food among Generation Z consumers in Jakarta. The research approach used is quantitative with a survey method. Data collection was conducted by distributing questionnaires to 150 Generation Z respondents residing in Jakarta. The sampling technique utilized a non-probability sampling method with a purposive sampling technique, along with an even 6-point Likert scale. The data analysis technique employed in this study is Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) assisted by SmartPLS 4.0 software. The direct effect hypothesis testing results indicate that the trust variable has a positive and significant effect on purchase intention. Conversely, the variables of food content, E-WOM, and perceived value are proven to have no significant direct effect on the purchase intention of Generation Z consumers toward viral food. The practical implications of this study emphasize that conventional marketing strategies that rely solely on content visual aesthetics, the quantity of online reviews, or price wars are no longer effective when standing alone.